Clostridioides difficile infection after extracorporeal membrane oxygenation support for acute myocardial infarction: a case report - Hu, Yanan; Hu, Chang; Jiang, Jun; Zhang, Jing; Li, Yiming; Peng, Zhiyong (Frontiers in Medicine, 2023)
Introduction: Restored cardiopulmonary function is efficiently achieved by utilizing extracorporeal membrane oxygenation (ECMO). Nevertheless, the incidence of Clostridioides difficile infection (CDI) associated with ECMO is relatively uncommon. Case presentation: In this report, we present the case of a 59-year-old male with severe chest pain due to acute myocardial infarction, subsequently necessitating ECMO support. During the first day of hospitalization, pulmonary infections were observed, and piperacillin-tazobactam was prescribed for 7 days at low dosages. However, the patient developed severe diarrhea four days later. After ruling out common pathogens, we suspected the occurrence of CDI and performed genetic testing for C. difficile toxin, confirming our diagnosis. The prescription of vancomycin resulted in slight improvement, while fecal microbiota transplantation (FMT) proved to be more effective. Conclusion: In this case, temporary application of ECMO was applied, and the anti-infective treatment relied on the use of antibiotics at short-term, low-dose, and low CDI risk. Hence, the occurrence of CDI was considered an uncommon event, which may serve as a reference for future cases.